COVID-19 Accelerating Academic Teachers’ Digital Competence in Distance Teaching - Myyry, Liisa; Kallunki, Veera; Katajavuori, Nina; Repo, Saara; Tuononen, Tarja; Anttila, Henrika; Kinnunen, Päivi; Haarala-Muhonen, Anne; Pyörälä, Eeva (Frontiers in Education, 2022)
This study examines, using a cross-sectional approach, the digital competence of academic teachers at a time when teaching shifted to digital distance learning at the start of the COVID-19 pandemic. Teachers from different academic fields at a large multidisciplinary Finnish university (N = 265) responded to a questionnaire about the purposes for which they use digital tools in teaching, how they evaluated their competence at distance teaching during the lockdown of March-May 2020 and their beliefs about distance teaching. The respondents used digital tools in teaching mostly for delivering information. According to their evaluations, their competence in distance teaching increased during the early stages of COVID-19 pandemic in 2020, but their beliefs about distance teaching did not relate to the feelings of competence. Respondents with no experience in distance teaching before the lockdown evaluated their competence as having increased more than did respondents with previous experience. The implications of the findings for understanding competence development are then discussed.